Az EU pénzügyi érdekeinek védelme, fókuszban a korrupció elleni szervezete - Balla, Zsuzsa (Debreceni Jogi Műhely, 2015)
Nowadays in these economical hard times it is very important to manage the public money efficiently. On the one hand it is a demand in the memberships countries and in the budget in the Europian Union. On the other hand it is a requirement from the oridnary people too. Actually the Europian Union takes part in the struggle against corruption. In fact the Europian Union has a strategy of struggle against corruption and cheating. The EU focuses on two fileds of strugggle against corruption, one of both is the budget of EU and the other is the public procurements. In this study I am dealing with the strategy of struggle against corruption, the main institutes and the main regulations.